Kegentingan Memaksa Atau Kepentingan Penguasa (Analisis Terhadap Pembentukan Peraturan Pemerintah Pengganti Undang-Undang (PERPPU)) - Muhammad Siddiq (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2014)
The arguable on explanation of circumstances of compelling crisis in making PERPPU (emergency law), has a possibility to create abuse of power. President, as an executive possessors in Indonesian constitutional law, has fully given absolute subjective rights in creating PERPPU. President is the only one person who has authority to interpret circumstances of compelling crisis regarding on government condition, whether it is in a good condition or not. Due to PERPPU characteristics is very subjective, it has possibility to mislead from its main meaning and purpose. It could be possible that president personal interest might be accommodated in a PERPPU, because of his authority in making PERPPU. For the time being, there is no regulation which interpret clearly circumstances of compelling crisis and its requirement, to explain whether the situation is in emergency or not. Because of that, if it does not have special regulation, PERPPU might have possibility to abuse by irresponsible person as a tool to achieve his personal purposes.